2015
DOI: 10.1016/j.jvs.2015.03.023
|View full text |Cite
|
Sign up to set email alerts
|

The value and economic analysis of routine postoperative carotid duplex ultrasound surveillance after carotid endarterectomy

Abstract: Background Several studies have reported on the role of postoperative duplex ultrasound surveillance after carotid endarterectomy (CEA) with varying results. Most of these studies had a small sample size or did not analyze cost-effectiveness. Methods We analyzed 489 of 501 CEA patients with patch closure. All patients had immediate postoperative duplex ultrasound examination and were routinely followed up both clinically and with duplex ultrasound at regular intervals of 1 month, 6 months, 12 months, and eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Moreover, the value of duplex after CEA for stroke prevention is still a subject of discussion and a customized follow-up in low-risk patients seems justified. 22,23 Third, hypertension was based on either the blood pressure at the outpatient clinic, as measured by the anesthesiologist preoperatively or by the use of medications. We acknowledge that a limited number of measurements is insufficient to properly diagnose patients for hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the value of duplex after CEA for stroke prevention is still a subject of discussion and a customized follow-up in low-risk patients seems justified. 22,23 Third, hypertension was based on either the blood pressure at the outpatient clinic, as measured by the anesthesiologist preoperatively or by the use of medications. We acknowledge that a limited number of measurements is insufficient to properly diagnose patients for hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Under this prism and if cost-effectiveness is in demand, policies of duplex scan surveillance at 1 month and then at 1-to 2-year intervals should be implemented. 40,41 Such long intervals should be counterbalanced against the benefits of encouraging more frequent patient follow-up, including careful reassessment of risk factors and medical treatment optimization.…”
Section: Discussionmentioning
confidence: 99%
“…This surveillance protocol detected only four patients with $80% restenosis, raising concerns about the unrealistic overuse of surveillance ultrasound assessments. 41 We are currently implementing surveillance at 1 month and annually thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…This notion, however, is increasingly challenged because of the decreasing and selective role for intervention in otherwise asymptomatic patients. 462,590,[594][595][596] A surveillance protocol is meaningful when anticipated results are likely to alter a medical or interventional treatment plan in a cost-effective manner.…”
Section: Postcarotid Intervention Surveillance: Post Cea and Post Ste...mentioning
confidence: 99%
“…The authors challenged the need for surveillance as not cost-effective and suggested decision making based on severity of the contralateral carotid. 596…”
Section: Surveillance For Restenosismentioning
confidence: 99%